Variants in clopidogrel-relevant genes and early neurological deterioration in ischemic stroke patients receiving clopidogrel - Xingyang Yi; Qiang Zhou; Yongyin Zhang; Ju Zhou; Jing Lin (BMC Neurology, 2020)
Abstract Background Early neurological deterioration (END) is common in acute ischemic stroke (IS). However, the underlying mechanisms for END are unclear. The aim of this study was to evaluate the associations of 16 variants in clopidogrel-relevant genes and interactions among these variants with END in acute IS patients receiving clopidogrel treatment. Methods We consecutively enrolled 375 acute IS patients between June 2014 and January 2015. Platelet aggregation was measured on admission and after the 7–10 days of clopidogrel treatment. The 16 variants in clopidogrel-relevant genes were examined using mass spectrometry. The primary outcome was END within the 10 days of admission. Gene-gene interactions were analyzed by generalized multifactor dimensionality reduction (GMDR) methods. Results Among the 375 patients, 95 (25.3%) patients developed END within the first 10 days of admission. Among the 16 variants, only CYP2C19*2 (rs4244285) AA/AG was associated with END using single-locus analytical approach. GMDR analysis revealed that there was a synergistic effect of gene-gene interactions among CYP2C19*2 rs4244285, P2Y12 rs16863323, and GPIIIa rs2317676 on the risk for END. The high-risk interactions among the three variants were associated with the higher platelet aggregation and independent predictor for END after adjusting for the covariates (hazard ratio: 2.82; 95% confidence interval: 1.36–7.76; P = 0.003). Conclusions END is very common in patients with acute IS. The mechanisms leading to END are most likely multifactorial. Interactions among CYP2C19*2 rs4244285, P2Y12 rs16863323, and GPIIIa rs2317676 may confer a higher risk for END. It was very important to modify clopidogrel therapy for the patients carrying the high-risk interactive genotypes. Clinical trial registration information The study described here is registered at http://www.chictr.org/ (unique Identifier: ChiCTR-OCH-14004724 ). The date of trial registration was May 30, 2014.